Nonfunctional requirements validation - A game theoretic approach - Papadopoulou, Vicky; Gregoriades, Andreas (My University, 2009)
Network Security requirements have recently gained widespread attention in the requirements engineering community. Despite this, it is not yet clear how to systematically validate these requirements given the complexity and uncertainty characterizing modern networks. Traditionally, network security requirements specification has been the results of a reactive process. This however, limited the immunity property of the software systems that depended on these networks. Security requirements specification prerequisite a proactive approach. Networks' infrastructure is constantly under attack by hackers and malicious software that aim to break into computers. To combat these threats, network designers need sophisticated security validation techniques that will guarantee the minimum level of security for their future networks. To that end, this paper presents a game-theoretic approach to security requirements validation. An introduction to game theory is presented along with a case study that demonstrates the application of the approach in a hypothetical network topology.
Keywords: Future networks; Malicious software; Network designer; Network topology; Software systems; Security requirements